The alcohol dehydrogenases of Bacillus stearothermophilus - Robinson, Glynis A. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2001)
A 1.5-kb fragment of Bacillus stearothermophilus DSM 2334 DNA was subcloned into pUC18, and the nucleotide sequence was determined. The fragment contained a complete open reading frame that encoded a 339-residue amino-acid sequence. The deduced amino-acid sequence was typical of a bacterial, NAD+- dependent, alcohol dehydrogenase (ADH). Seven residues that constitute the ligands to two zinc ions in horse liver ADH were strictly conserved. The N-terminal amino- acid sequence (forty residues) of purified B stearothermophilus DSM 2334 alcohol dehydrogenase (ADH 2334) was determined. The amino-acid sequence-data confirmed that the nucleotide sequence of the complete open reading frame was that of the gene (adh2334) that encodes ADH 2334.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin